Improving Students’ Vocabulary Mastery Through Listening English Songs of SMA Negeri 1 Torue - Nandita, Dinda; Thamrin, Nur Sehang; Anggreni, Afrillia; Nadrun, Nadrun (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aimed to improve the vocabulary mastery of tenth-grade students at SMA Negeri 1 Torue through an innovative learning method, namely by listening English songs. The low ability of students to remember, pronounce, and use new vocabulary in the correct context was the problem of the students expanding their vocabulary. This research used a quasi-experimental research design involving two groups: the experimental group that was taught using songs and the control group that was taught using conventional methods. The population is 369 students. A total of 60 students from classes XB and XC participated in this research, and data were collected through a pre-test and post-test to measure the improvement of students’ vocabulary mastery, especially on verbs, nouns, and adjectives. The results of the research present a significant increase in students’ vocabulary mastery after utilizing English songs. The mean post-test score of the experimental group increased from 45 to 89, while the control group only increased from 46 to 76. The hypothesis test using a t-test indicated that the t-value (6.14) was higher than the t-table value (2.042), which suggested that listening to English songs is effective in improving students’ vocabulary mastery. This research concludes that the use of songs as a learning medium could create a fun learning atmosphere and increase students’ motivation to learn English.